Pharmacological labour pain interventions: South African midwives’ perspective - LE. Parkies; D. Murray; U. B. Okafor (BMC Nursing, 2024)
Abstract Background Women of childbearing age feel great about giving birth, but the pain could be excruciating depending on their pain tolerances. Midwives requires obstetrical knowledge and skills such as pain management during labour and safety. We explored midwives’ perspectives on the utilisation of pharmacological pain alleviation interventions during labour in selected hospitals in Matjhabeng Municipality, Free State province, South Africa. A qualitative study was undertaken, involving a sample of ten midwives, using a semi-structured interview guide. The interviews were audio-recorded and transcribed verbatim. Tesch’s open coding data analysis method was applied to analyse the data. The midwives were restricted to use Pethidine and Phenergan prescribed by doctors for labour pain relief, which disrupted labour pain management and obliged them either to wait for a physician or follow telephone instructions. According to the midwives, women taking Pethidine and Phenergan encountered adverse effects and discomfort. Midwives identified high workload, inadequate personnel, lack of skill and knowledge, lack of medication availability, and lack of infrastructure as the primary challenges of administering pharmacological methods to women in labour. The lack of standing orders, which delays the administration of medications pending a physician’s prescription, constituted an additional difficulty. In the instance that Pethidine and Phenergan were unavailable or ineffective for some women, the midwives recommended that women be administered alternative pharmacological pain relievers. They also advocated for institutionalization of pharmacological guidelines allowing them to use their discretion when treating labour pain. Midwives can only utilise a few standardised and regulated pharmacological medications for labour pain management. The midwives’ ability to administer pharmacological pain relief during labour was hampered by a high workload burden, insufficient staff, lack of skill and understanding, drug unavailability, and inadequate infrastructure. Midwives advocated for supported guidelines that would allow them to treat labour pain at their discretion. Intersectoral stakeholders are required to improve midwife skills and attitudes. Health facilities need to train and supply analgesics to midwives. Midwives ought to be familiar with pharmacological pain relievers.